The Role of Indonesia in Mitigating the Humanitarian Impact of the War in Gaza through Humanitarian Assistance - Chandra, Arlina Alfiani; Sukendro, Achmed; Uksan, Arifuddin; Widodo, Pujo; Anas, Muhammad Riza Fathu (Journal of Law, Politic and Humanities, 2024)
The outbreak of the Hamas-Israel war in October 2023 resulted in significant humanitarian impacts, including tens of thousands of civilian casualties, destruction of homes, places of worship, and hospitals, heightened potential for diseases, and deep-seated trauma. The humanitarian impact in Gaza became a global issue requiring immediate attention, including from Indonesia. This research aimed to explore the Hamas-Israel conflict, highlighting Indonesia’s active role in alleviating humanitarian impacts in Gaza through humanitarian assistance. Descriptive qualitative methodology was used in this research to provide a comprehensive understanding of the topic. Data were collected through a literature review from relevant books, journals, and websites to elucidate Indonesia’s role in mitigating the humanitarian impact of the Gaza conflict through humanitarian assistance. The study employed Conflict Theory, Constructivist Theory, and Humanitarian Assistance Concepts for analysis. The study results revealed that Indonesia had provided humanitarian aid covering basic needs such as food, water, and medical supplies, alongside funding for hospital repairs delivered via sea and air routes in collaboration with Egypt and Jordan. Indonesia guided by its national goal to achieve world peace is committed to give humanitarian assistance throughout the Hamas-Israel war while supporting a two-state solution as a conflict resolution.